ANTIOXIDANT AND HEPATOPROTECTIVE EFFECTS OF VIRGIN COCONUT OIL AT MAXIMUM PHYSICAL ACTIVITY - APOLLO SINAGA, FAJAR; HARAHAP, URIP; SILALAHI, JANSEN; SIPAHUTAR, HERBERT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The purpose of this study was to determine the protective effects of virgin coconut oil (VCO) treatment on hepatic oxidative stress and antioxidant defenses after maximum physical activity. Methods: This study used 24 healthy male rats. The rats were divided into four groups randomly consisted of six rats in each group. The control group (P0) was given 2 mL water, the treatment groups (VCO-1, VCO-2, and VCO-4) were given VCO 1 ml/200 g BW, 2 ml/200 g BW, and 4 ml/200 g BW, respectively, per day using gavage spuit. The rats were trained to swim for a month, 30 min/day in the 1st week, 35 min/day in the 2nd week, 40 min/ day in the 3rd week, and 45 min/day in the 4th week. After 28 days, the rats were forced to perform the maximal activity by putting the rats in water with no exit. Blood samples were collected immediately after the maximum physical activity, and then, all rats were killed and liver tissues were collected. The malondialdehyde (MDA), glutathione peroxidase (GPx), and serum glutamic-oxaloacetic transaminase and serum glutamic-pyruvate transaminase level were then measured. Results: VCO increased swimming time to exhaustion, levels of GPx in the liver, which were accompanied by corresponding decreases in the MDA, alanine transaminase, and aspartate transaminase content. Conclusion: The results from this study indicate that VCO is effective in the prevention of oxidative stress following maximum physical activity.